2015
DOI: 10.1097/aci.0000000000000197
|View full text |Cite
|
Sign up to set email alerts
|

Linking immune responses with fibrosis in allergic eye disease

Abstract: Purpose of review Here we explore an emerging theme in the literature, which is the role of dendritic cells in the causation of fibrosis. To fully appreciate this pathway to disease, we also review the most recent literature regarding dendritic cell biology as it pertains to ocular surface tissues. Based on this information we propose a unifying hypothesis for how dendritic cells may cause conjunctival fibrosis in the allergy setting. Recent Findings Work in models of airway remodeling and liver fibrosis has… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 64 publications
(78 reference statements)
0
7
0
Order By: Relevance
“…Wound healing mechanisms in the conjunctiva are involved in the pathology of various ocular diseases, and in the outcomes of ocular surgeries, including for pterygium and glaucoma [1][2][3][4][5]. Among the numerous cell types that contribute to wound closure, fibroblasts have been known to play a particularly important role by transdifferentiation into myofibroblasts.…”
Section: Introductionmentioning
confidence: 99%
“…Wound healing mechanisms in the conjunctiva are involved in the pathology of various ocular diseases, and in the outcomes of ocular surgeries, including for pterygium and glaucoma [1][2][3][4][5]. Among the numerous cell types that contribute to wound closure, fibroblasts have been known to play a particularly important role by transdifferentiation into myofibroblasts.…”
Section: Introductionmentioning
confidence: 99%
“…The interplay between the immune system, inflammation and fibrosis has been well-documented 13 , 63 , 64 . Recently, work has highlighted the role of the fibrocyte, a leukocyte subtype that expresses both CD45 and collagen I, in both wound healing and the fibrotic response 65 67 .…”
Section: Resultsmentioning
confidence: 99%
“…Among the alternative features of conjunctival barrier function, their permeability is also recognized to be an important factor for drug delivery to the posterior segment of the eye after the instillation of ocular drugs [ 2 ]. In terms of the clinical aspects of subconjunctival fibrosis, it has been suggested that the regulation of wound healing in the conjunctiva is of great importance in terms of the surgical outcomes of ocular surface-related diseases, such as pterygium and glaucoma [ 3 , 4 , 5 , 6 , 7 ]. In fact, conjunctival scarring at the operative site may adversely induce poor success rates in the subsequent trabeculectomy [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%